2023
DOI: 10.1186/s12906-023-03861-9
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic inhibitory activity of Glycyrrhizae Radix and Rubi Fructus extracts on biofilm formation of Streptococcus mutans

Abstract: Background Streptococcus mutans is a bacterium that causes oral diseases. Plaque, a biofilm produced by S. mutans and other bacteria, makes it difficult to remove cariogenic oral microorganisms, including biofilm producers. Glucan synthesis by glucosyltransferase is one of the mechanisms underlying plaque formation. This study demonstrates the effectiveness of inhibiting biofilm formation by interfering with the glucosyltransferase activity of S. mutans using edible herbal medicines. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Through screening various plant extracts, they identified GLY as a compound that, when combined with other extracts, inhibits S. mutans cell growth, biofilm formation, and glucan synthesis by GTase. Consequently, this inhibitory action impedes dental biofilm formation, as illustrated in their findings [ 47 ] ( Figure 1 B).…”
Section: In Vitro Antimicrobial Effect Of Glymentioning
confidence: 85%
See 2 more Smart Citations
“…Through screening various plant extracts, they identified GLY as a compound that, when combined with other extracts, inhibits S. mutans cell growth, biofilm formation, and glucan synthesis by GTase. Consequently, this inhibitory action impedes dental biofilm formation, as illustrated in their findings [ 47 ] ( Figure 1 B).…”
Section: In Vitro Antimicrobial Effect Of Glymentioning
confidence: 85%
“…This results in an influx of protons into the cell, subsequently reducing intracellular acidity. Additionally, GLY inhibits glycolysis-related enzymes, effectively impeding the glycolytic process and thereby restricting the growth of S. mutans [ 47 ]. Liu et al found that GLY exhibits a significant and dose-dependent inhibition of both the proliferation and acid production of S. mutans [ 48 ].…”
Section: In Vitro Antimicrobial Effect Of Glymentioning
confidence: 99%
See 1 more Smart Citation